2018
DOI: 10.3892/ol.2018.9851
|View full text |Cite
|
Sign up to set email alerts
|

Differences in colorectal cancer surveillance epidemiology and screening in the WHO European Region

Abstract: The aim of this study was to describe the Colorectal Cancer (CRC) burden and prevention actions in 53 countries of the World Health Organization (WHO) European Region (ER). Multiple correspondence analysis was applied to examine the association among the following variables: Measures of occurrence; type of screening programme; existence of cancer registries; data quality and; and gross national income (GNI) level. The study demonstrated clear differences according to GNI: low-middle income (LMI) countries show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…Furthermore, CRC screening based on stool testing and flexible sigmoidoscopy has reduced CRC-related death rate by 16% and 22%−31%, respectively (34,35). The WHO ER examined the association factors in CRC surveillance epidemiology and screening, and found that available resources (as measured by gross national income) appear to be the major factor in the Colorectal Cancer Surveillance Epidemiology and Screening (36). According to results from studies focused on cost-effectiveness, CRC screening was cost-effective compared with no screening (37).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, CRC screening based on stool testing and flexible sigmoidoscopy has reduced CRC-related death rate by 16% and 22%−31%, respectively (34,35). The WHO ER examined the association factors in CRC surveillance epidemiology and screening, and found that available resources (as measured by gross national income) appear to be the major factor in the Colorectal Cancer Surveillance Epidemiology and Screening (36). According to results from studies focused on cost-effectiveness, CRC screening was cost-effective compared with no screening (37).…”
Section: Discussionmentioning
confidence: 99%
“…The screening programs aim to identify patients with precancerous lesions or those with resectable CRC stages 0, I, and II, who have a generally better prognosis than symptomatic patients with the pre-existing disease [3]. Despite screening programs, many patients are diagnosed in the stages III and IV of CRC that lead to a worse overall prognosis [4]. According to data from National Cancer Institute from the United States of America (USA) [5], five years survival rates for stage IV account only for 12% at colon cancer (CC) and 13% at rectal cancer (RC), while detection at an early stage I can increase the chance to survive up to 92% at CC and 88% at RC [6].…”
Section: Introductionmentioning
confidence: 99%
“…This data could be considered as an indicator of awareness with respect to food education policies and social habits which, however, appear to be very different between different nations, as in the case of Europe [61]. It is well known how the adoption of a healthy diet, with an adequate intake of carbohydrates, greatly reduces cardiovascular risk and obesity [62,63]. With respect to the consumption of soft drinks, it is noted that in Narain’s meta-analysis there is an increased risk for ischemic stroke in women [43].…”
Section: Discussionmentioning
confidence: 99%